Inconstitucionalidad de las normas colombianas que permiten la explotación de hidrocarburos mediante el método de fracking (2016)
This assignment search to do an analysis if are or not unconstitutional the norm that describe the terms to grant or not environmental license to advance the exploration and hydrocarbons exploitation in Colombia by Fracking method. To do this we start detailing what the method Fracking, or hydraulic fracturing, which makes it different from traditional methods; what is the biotic and abiotic ecosystem and how it can be contaminated for hand of man especially for the dumping hydrocarbon and contaminated water tha damage the atmosphere, groundwater and surface; alike done a route for the treatment that have affected these standards, finally is confronted with the principles, fundamental rights and collective rights to enjoy a healthy environment in order to analyze its constitutionality and how it can be applied for prevention principles and caution to stop fracking system until scientifically proven that this technique doesn´t generate serious environmental problems